A multi-stakeholder approach to sustainable rural tourism development: the heritage trail of Dolenjska & Bela krajina Case Study - Koščak, Marko; O’Rourke, Tony (Sensos-e, 2019)
One of the beneficial methodologies for growing and developing a level of tourism, which is sustainable and enhances the totality of local and regional environments, is a multi-stakeholder approach to tourism development. In this paper, we propose that sustainable rural development takes an integrated approach in the development process, supported by and benefiting from a core of multiple stakeholders. It is clear that: a) Entrepreneurship, in a bottom-up model may have a huge impact on rural micro-economies at a local level. It drives wealth creation and expands employment in a measurable, tangible and transparent way; b) Multi-stakeholder tourism projects benefit ownership transformation processes by forcing public, private, and social entities to work for the common benefit. Because of the bottom up approach the measurable value is also more obvious; c) By engaging local public agencies, the dimension of environmental planning and protection can be assured. In this way the sustainable nature of tourism and its impact on the local environment can be assessed and given due priority. D) At the same time, entrepreneurs comprehend the value of co-operation. An integrated model enables participants to benefit from the totality and complexity of resources and skills held by all stakeholders. Full Article